Formyl Peptide Receptor 2 Activation Ameliorates Dermal Fibrosis and Inflammation in Bleomycin-Induced Scleroderma - Park, Gyu Tae; Kwon, Yang Woo; Lee, Tae Wook; Kwon, Seong Gyu; Ko, Hyun-Chang; Kim, Moon Bum; Kim, Jae Ho (Frontiers in Immunology, 2019)
Systemic sclerosis is a profibrotic autoimmune disease mediated by the dysregulation of extracellular matrix synthesis. Formyl peptide receptor 2 (Fpr2) is a G protein-coupled receptor that modulates inflammation and host defense by regulating the activation of inflammatory cells, such as macrophages. However, the role of Fpr2 in the development and therapy of scleroderma is still unclear. The present study was conducted to investigate the effects of Fpr2 activation in the treatment of scleroderma fibrosis. We found that intradermal administration of WKYMVm, an Fpr2-specific agonist, alleviated bleomycin-induced scleroderma fibrosis in mice and decreased dermal thickness in scleroderma skin. WKYMVm-treated scleroderma skin tissues displayed reduced numbers of myofibroblasts expressing α-smooth muscle actin, vimentin, and phosphorylated SMAD3. WKYMVm treatment attenuated macrophage infiltration in scleroderma skin and reduced the number of M2 macrophages. The therapeutic effects of WKYMVm in scleroderma-associated fibrosis and inflammation were completely abrogated in Fpr2 knockout mice. Moreover, WKYMVm treatment reduced the serum levels of inflammatory cytokines, such as tumor necrosis factor-α and interferon-γ, in the scleroderma model of wild-type mice but not in Fpr2 knockout mice. These results suggest that WKYMVm-induced activation of Fpr2 leads to alleviation of fibrosis by stimulating immune resolution in systemic sclerosis.